2006
DOI: 10.1149/1.2215586
|View full text |Cite
|
Sign up to set email alerts
|

Drying Effects on Corrosion Properties of Cr(VI)- and Cr(III)- Treated Electrogalvanized Steel

Abstract: Drying effects on corrosion performance of Cr(VI)-and Cr(III)-treated electro-galvanized steel have been studied in NaCl solution using potentiodynamic measurements and electrochemical impedance spectroscopy (EIS). The Cr(VI) and the Cr(III) treated specimens were dried at three different temperatures: 60, 110 and 210°C. The surface layers were investigated using SEM, AES and XPS. The results show that the drying temperature not only affects the morphology of the surface layer, but also changes the chromium ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In Figure , typical curve-fitted Cr 2p core level spectra of 3% and 15% Cr/Co 3 O 4 catalysts are shown. Observed Cr 2p 3/2,1/2 peaks around 576.2 and 585.9 eV with 9.7 eV spin–orbit separation correspond to Cr 3+ species. , Weak component peaks at 578.6 and 588.3 eV with 9.7 eV spin–orbit separation can be attributed to either Cr 3+ species in Cr­(OH) 3 or Cr 6+ species. , The possibility of formation of hydroxide species may be higher as a component peak related to hydroxide species is observed in O 1s core level spectra (discussed later). It has been noticed that surface concentrations of hydroxide/Cr 6+ are observed to be in 10–23% in these catalysts.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In Figure , typical curve-fitted Cr 2p core level spectra of 3% and 15% Cr/Co 3 O 4 catalysts are shown. Observed Cr 2p 3/2,1/2 peaks around 576.2 and 585.9 eV with 9.7 eV spin–orbit separation correspond to Cr 3+ species. , Weak component peaks at 578.6 and 588.3 eV with 9.7 eV spin–orbit separation can be attributed to either Cr 3+ species in Cr­(OH) 3 or Cr 6+ species. , The possibility of formation of hydroxide species may be higher as a component peak related to hydroxide species is observed in O 1s core level spectra (discussed later). It has been noticed that surface concentrations of hydroxide/Cr 6+ are observed to be in 10–23% in these catalysts.…”
Section: Resultsmentioning
confidence: 95%
“…43,44 Weak component peaks at 578.6 and 588.3 eV with 9.7 eV spin−orbit separation can be attributed to either Cr 3+ species in Cr(OH) 3 or Cr 6+ species. 45,46 The possibility of formation of hydroxide species may be higher as a component peak related to hydroxide species is observed in O 1s core level spectra (discussed later). It has been noticed that surface concentrations of hydroxide/ Cr 6+ are observed to be in 10−23% in these catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The Cr 2p 3/2,1/2 peaks found at 576.2 and 585.8 eV with 9.6 eV spin–orbit separation are attributed to Cr 3+ species . The low-intensity component peaks at 578.7 and 588.5 eV with 9.8 eV spin–orbit separation correspond to either Cr 3+ species in Cr­(OH) 3 or Cr 6+ species. , The formation of hydroxide species may be more plausible, as a component peak associated with hydroxide species is found in the O 1s core level spectrum. However, it is evident from XPS studies that Cr 3+ species are the dominant species in the CoCr 2 O 4 catalyst.…”
Section: Resultsmentioning
confidence: 97%
“…Here, surface concentrations of Fe 2+ and Fe 3+ species or Cr 6+ species. 55,56 The formation of hydroxide species may be more plausible, as a component peak associated with hydroxide species is found in the O 1s core level spectrum. However, it is evident from XPS studies that Cr 3).…”
Section: Resultsmentioning
confidence: 99%
“…Our work does not demonstrate the link between the susceptibility to cracking of the conversion layer under vacuum and its corrosion resistance, as has been established by other researchers. 25,33,65,66 Laget et al 33 studied chromate conversion coating, and concluded that the dehydration of the coatings explains the losses in corrosion resistance observed after aging. Heller et al 65 found that inhibiting cracking improves the corrosion resistance of cerium conversion coatings but that elimination of cracking alone does not guarantee a good corrosion protection.…”
Section: Discussionmentioning
confidence: 99%